Pancasila dan pendidikan antikorupsi: Implementasi nilai Pancasila dalam pendidikan antikorupsi di perguruan tinggi - tamami, mohammad nuri (Maliki Interdisciplinary Journal, 2025)
Pancasila, as the foundation of the state and the moral compass of the Indonesian nation, plays a crucial role in shaping the character of its citizens. However, the prevalence of corruption indicates a gap between Pancasila’s values and the existing social reality. This study aims to analiyze the implementation of Pancasila values in anti-coruption education at the univercity level as an effort to build a generation with integrity. A literature review method was employed by examining academice sources related to Pancasila-based anti-corruption education. The findings reveal that the integration of values such as honesty, responsibiliity, justice, and discipline through the Pancasila Education course contributes to forming students’ anti-corruption character. Contextuall learning models, such as Project Citizen, have proven effective in internalizing these values through direct experience. Anti-corruption education based on Pancasila in higher education serves as a strategic approach to fostering moral and ethical awareness to create a just, honest, and civilized society.